Determinants of voluntary smoke- free home among nonsmoking women in Alor Gajah, Melaka - Shahar, Noor Syazwani; Muthiah, Sri Ganesh; Kadir @ Shahar, Hayati (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2019)
Second hand smoke exposure to cigarette smoke leads to many medical conditions including asthma and lung cancer. Women are the most vulnerable adults of passive smoking at home. Even though Malaysia had its own smoke- free policy, the smoke- free home is voluntary in nature. Thus, this study was aimed to explore the practice of voluntary smoke- free- home among women in Alor Gajah and its determinants. Methods: A cross-sectional study based on multistage sampling was conducted among 180 non- smoking women in areas implemented Community Intervention Program (KOSPEN), which emphasized on healthy lifestyle, in Alor Gajah, Melaka from April 2018 to May 2018. Data on sociodemographic characteristic, characteristic of second hand smoke (SHS) exposure at home, knowledge, attitude and avoidance behaviour from SHS were collected using questionnaires. The data were then analysed using IBM Statistical Package for Social Science (SPSS) version 24.0 involving descriptive and inferential statistics. Results: Majority of the respondents practised smoke- free home (72.8%). The predictors of smoke- free home were those who attained higher education (AOR= 11.939, 95% CI 1.175- 121.277), did not live with any children (AOR= 3.546, 95% CI 0.985- 12.765) and lived with smokers other than their husband (AOR= 3.793, 95% CI 1.192- 12.076). Conclusion: Education level and household factors were significant predictors of smoke- free home. Thus, few measures were suggested to increase tobacco bans at home among women including periodic health programs, community empowerment programs and creating smoke- free housing.